(untitled) (KASBIT Business Journal, 2026)
Objectives: The increasing demand for organizations to maintain a competitive advantage in a dynamic global market has brought talent management (TM) and innovation to the forefront of strategic discussion. In the pharmaceutical sector, talent management practices are predominantly vigorous due to the industry’s competitive nature and the prerequisite for sustainable competitive advantages, additionally in low- and middle-income countries like Pakistan might present unique challenges and opportunities for executing talent management practices meritoriously. This research study pursues to deliver practical takeouts for all stakeholders of Pakistan’s pharmaceutical industry, including policymakers, regulatory bodies, human resources department, and industry’s leadership, to successfully answer this persistent problem. Methods: A quantitative Cross-sectional research design was performed, participants for this study were pharmaceutical staff who were associated with the pharmaceutical sector within Pakistan, the data collection tool was a survey questionnaire, data was analyzed using PLS-SEM and we performed a regression analysis to analyze the data. Results: The results reveal a significant positive association between Talent Management dimensions and innovative work behavior. Moreover, Employee Development dimension of Talent Management exhibited the highest predictive strength regarding organizational innovation. Conclusions: The findings confirms that a robust and strategic approach to overseeing talent, encompassing elements like performance evaluation, career development chances, and pay for performance systems is a chief precursor to both incremental and radical innovation capabilities.